ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN GUNUNGKIDUL DIY - Erlinda Nur Khasanah; Fauzi Rifqi Aldiyanto (Jurnal Akuntansi dan Pajak, 2023)
Along with increasing development to support the existing natural and cultural tourism potential, Gunungkidul Regency is expected to manage and maximize this potential for the progress of region. One of these potentials can be obtained from sources of revenue originating from regional taxes. Thus, it is necessary to do an analysis to see how far the local tax contribution to Gunungkidul Regency's original local government revenue. In addition, this study aims to measure level of effectiveness of local tax revenues and to analyze the efforts of Gunungkidul local government to increase the potential for local tax revenues. This research method used is a quantitative method with secondary data sources in the form of regional financial reports of Gunungkidul Regency for 2017-2021. The results showed that contribution ratio of local taxes to original local government revenue of Gunungkidul Regency in 2017-2021 reached an average contribution of 22.18%. This ratio is still relatively small in influencing original local government revenue. The results of subsequent research show that the average ratio of effectiveness of local taxes for five years can be said to be good because it reaches of 109.24%. One effort to increase local tax collection in Gunungkidul Regency is by using SIPAPAH application. However, this application is still not optimal because people still lack understanding of this application and technological development.